KOMUNIKASI DALAM PENANGANAN KELUHAN PASIEN DI RUMAH SAKIT KHUSUS BEDAH ROPANASURI KOTA PADANG - Fadhil Ahmad; Ernita Arif; Sarmiati (Halu Oleo University, 2025)
Evaluation of complaint handling is very important to improve the quality of service to patients in hospital institutions. This study aims to analyze the implementation of complaint handling and communication barriers in complaint handling at Ropanasuri Surgical Specialty Hospital, Padang, West Sumatra. Qualitative methods through semi-structured interviews were used to explore information related to handling patient complaints. Data analysis was carried out using triangulation techniques, namely data reduction, data presentation, and conclusion drawing. The results revealed that complaint handling at Ropanasuri Surgical Specialty Hospital has not been running optimally because there are still similar and repeated complaints by patients, both related to inadequate infrastructure, doctors who do come not according to schedule, and officers who are less capable of serving patients. The absence of a standard operating procedure for communication-related to handling patient complaints is believed to be the cause of the communication process not being maximized. Communication barriers that often occur are miscommunication between hospital staff and patients regarding referral period information, the wrong poly, and BPJS patients from outside the area who do not follow the correct procedures. This study emphasizes the importance of the existence of standard operating procedures as a guide for handling patient complaints and effective communication training specifically for employees at Ropanasuri Surgical Specialty Hospital.